2020
DOI: 10.1111/maps.13611
|View full text |Cite
|
Sign up to set email alerts
|

Fe‐redox changes in Itokawa space‐weathered rims

Abstract: Synchrotron Fe-K X-ray absorption spectroscopy and transmission electron microscopy have been used to investigate the mineralogy and Fe-redox variations in the space-weathered (SW) rims of asteroidal samples. This study focuses on the FIB lift-out sections from five Itokawa grains, returned by the Hayabusa spacecraft, including samples RB-QD04-0063, RB-QD04-0080, RB-CV-0011, RB-CV-0089, and RB-CV-0148. Each of the samples featured partially amorphized SW rims, caused by irradiation damage from implanted low ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The samples were stored in a nitrogen dry box but exposed to ambient air several times during transfer from the sample container to the epoxy stub. Overall, the material in the Itokawa particles is not oxidized, with EELS measurements of interior regions of grains showing only Fe 2+ present in olivine and pyroxene, consistent with previous XANES analyses of Itokawa HPx and LPx and with other LL OCs (Noguchi et al 2014a), although Hicks et al (2020) reported minor Fe 3+ in several samples. The formation of an oxidized rim due to laboratory exposure is consistent with XPS measurements of experimentally irradiated olivine, which have shown that initial metallic Fe formed during the experiment is quickly oxidized once removed from vacuum as oxygen from the atmosphere is able to interact with damaged and broken bonds in the material (Loeffler et al 2009).…”
Section: Oxidationsupporting
confidence: 88%
See 4 more Smart Citations
“…The samples were stored in a nitrogen dry box but exposed to ambient air several times during transfer from the sample container to the epoxy stub. Overall, the material in the Itokawa particles is not oxidized, with EELS measurements of interior regions of grains showing only Fe 2+ present in olivine and pyroxene, consistent with previous XANES analyses of Itokawa HPx and LPx and with other LL OCs (Noguchi et al 2014a), although Hicks et al (2020) reported minor Fe 3+ in several samples. The formation of an oxidized rim due to laboratory exposure is consistent with XPS measurements of experimentally irradiated olivine, which have shown that initial metallic Fe formed during the experiment is quickly oxidized once removed from vacuum as oxygen from the atmosphere is able to interact with damaged and broken bonds in the material (Loeffler et al 2009).…”
Section: Oxidationsupporting
confidence: 88%
“…The oxidation on most of the rims occurs to depths of 10-20 nm, similar to the depth of sulfur depletion in the troilite rim and consistent with the depth of greatest damage by hydrogen from the solar wind (Noguchi et al 2014b;Matsumoto et al 2020). Hicks et al (2020) recently reported oxidation of the space weathered rim in several Itokawa particles, with up to 14% more Fe 3+ in one olivine rim compared to the host grain, and confirmed metallic npFe 0 within the oxidized rim matrix. Their XANES measurements average over the full rim depth (~50 nm), and thus are consistent with our higher oxidation values at very shallow depths.…”
Section: Oxidationsupporting
confidence: 63%
See 3 more Smart Citations